2013
DOI: 10.1681/asn.2012101044
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Protects against Shiga Toxin–Triggered Apoptosis by Reversing the Imbalance between Bax and Bcl-xL

Abstract: Hemolytic uremic syndrome, a life-threatening disease often accompanied by acute renal failure, usually occurs after gastrointestinal infection with Shiga toxin 2 (Stx2)-producing Escherichia coli. Stx2 binds to the glycosphingolipid globotriaosylceramide receptor, expressed by renal epithelial cells, and triggers apoptosis by activating the apoptotic factor Bax. Signaling via the ouabain/Na,K-ATPase/IP3R/NF-kB pathway increases expression of Bcl-xL, an inhibitor of Bax, suggesting that ouabain might protect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 38 publications
2
42
0
2
Order By: Relevance
“…It is well documented that excessive uptake of albumin into RPTC triggers apoptosis 30,4143 and generation of pro-fibrotic factors, such as TGF-beta 44 . To determine the order by which these processes are initiated, we incubated RPTC with fatty acid and endotoxin-free albumin (10 mg/mL) for 2, 4, 8 and 18 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that excessive uptake of albumin into RPTC triggers apoptosis 30,4143 and generation of pro-fibrotic factors, such as TGF-beta 44 . To determine the order by which these processes are initiated, we incubated RPTC with fatty acid and endotoxin-free albumin (10 mg/mL) for 2, 4, 8 and 18 hours.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the ouabain signal may interfere with the apoptotic process by down-regulation of the apoptotic factor Bax and up-regulation of the anti-apoptotic factor Bcl-xl. 2530 Studies from us and other investigators have provided evidence for a tissue protective effect of ouabain 3036 .…”
Section: Introductionmentioning
confidence: 97%
“…ferrets infected orally with Escherichia coli O157:H7 (Woods et al, 2002), or newborn pigs infected orally E. coli O157:H7 or O26:H11 (Gunzer et al, 2002). C57BL/6 mice injected intraperitoneally with Shiga toxin 2 (Stx2) or with Stx2 þ LPS (Psotka et al, 2009) displayed increased proximal tubular cell apoptosis and loss of podocytes (Burlaka et al, 2013) or damage to collecting duct cells (Psotka et al, 2009), but not other characteristics of HUS. The only animal to date that presents full spectrum HUS induced by Stx or Stx2 challenge is the baboon (Taylor et al, 1999).…”
Section: Hemolytic Uremic Syndrome (Hus)mentioning
confidence: 99%
“…Stx2 has been shown to increase the expression of the pro-apoptotic factor Bax [10] and SubAB to induce a pathway depending of the pro-apoptotic proteins Bax/Bak [11] Aperia and her group [12] in 2013 showed that the exposure of rat proximal tubular cells to Stx2 produced massive apoptosis with up regulation of the apoptotic factor Bax, increased cleaved caspase-3, and down regulation of the survival factor Bcl-xL. Co-incubation with ouabain (OUA) prevented all these effects.…”
Section: Introductionmentioning
confidence: 99%